From crisis to opportunity: Environmental jolt, corporate acquisitions, and firm performance - WAN, William P. (Institutional Knowledge at Singapore Management University, 2009)
This study incorporates the external environmental context into the study of corporate acquisitions by examining the performance implications of corporate acquisitions during an environmental jolt that alters the levels of environmental munificence. We posit that compared to the periods before and after an environmental jolt, corporate acquisitions during a jolt would be positively related to firm performance. Furthermore, we suggest that organizational slack would improve firm performance and accentuate the positive relationship between corporate acquisitions and firm performance during an environmental jolt; however, it would have negative impact on firm performance and make the acquisition-performance relationship more negative before and after a jolt. Using the Asian Economic Crisis as a natural experiment, we found general support for our core arguments based on a sample of firms from Hong Kong and Singapore. Our work demonstrates that firms can capitalize on the opportunities created by the changes in an environmental jolt.